Assessment of corrosion-fatigue degradation of grade R4 steel sing an electrochemical-mechanical combined approach - Canut, Felipe Azevedo (2022)
Tese (doutorado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Mecânica, 2022.